The World Catalog of Biting Midges (Diptera: Ceratopogonidae): Additional Updates and Errata - Borkent, Art; Evenhuis, Neal L.; Dominiak, Patrycja (Zootaxa, 2025)
A list of corrections and the addition of new taxa described since Borkent & Dominiak (2020) published a catalog of the Ceratopogonidae of the world and Borkent et al. (2022) provided an update of corrections and new taxa is provided. We record a further 66 extant and 3 fossil species and 2 new fossil genera, as well as four new tribes that have also been proposed by Borkent (2024). A table recording the number of species in each genus and subgenus indicates that the family now includes 6346 extant and 303 fossil species and 107 extant and 23 fossil genera. The number of species names regarded as nomina dubia is now 189. Atrichopogon wirthi Szadziewski & Borkent, 2003 is considered a junior synonym of A. wirthorum Delécolle & Braverman, 1997, syn. nov. The fossil genus Nelohelea Szadziewski & Sontag is here placed in the tribe Washingtonheleini.